The Implementation of Project Based Learning Connected Wwth Digital Technology to Increase Students Speaking Competence of Madrasah Aliyah Negeri (MAN) Simalungun Regency - Basar Lolo Siahaan; Mungkap Mangapul Siahaan (STAI Hubbulwathan Duri, 2023)
Project based learning (PjBL) has become one of the innovative trends in education to create an exciting teaching-learning environment where the teachers become the facilitators to construct their students’ knowledge. This study aims to develop implementation Project Based Learning to increase students speaking competence. This study uses Four D model procedure. To enhance students speaking competence, this research also develops a syllabus, lesson plans and digital technology. This research investigates the implementation of PjBL by using digital apparatus which is connected with internet to increase students speaking competence of Madrasah Aliyah Negeri (MAN) Simalungun regency, North Sumatera Province, Indonesia. The validation of PjBL was carried out by three validators of each material experts and media experts. The feasibility study of PjBL products shows validity of 85% with very valid criteria. The result of the researches obtained an average score of 90%. The syllabus obtained an average score of 84%, lesson plans obtained an average score of 84%, and digital facilities obtained an average score of 85%. In conclusion, PJBL increases students speaking competence especially supported by digital facilities.